2009
DOI: 10.1158/0008-5472.can-08-4801
|View full text |Cite
|
Sign up to set email alerts
|

Kinome Profiling of Chondrosarcoma Reveals Src-Pathway Activity and Dasatinib as Option for Treatment

Abstract: Chondrosarcomas are notorious for their resistance to conventional chemotherapy and radiotherapy, indicating there are no curative treatment possibilities for patients with inoperable or metastatic disease. We therefore explored the existence of molecular targets for systemic treatment of chondrosarcoma using kinome profiling. Peptide array was performed for four chondrosarcoma cell lines and nine primary chondrosarcoma cultures with GIST882, MSCs, and colorectal cancer cell lines as controls. Activity of kina… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
89
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 43 publications
3
89
0
Order By: Relevance
“…NRAS mutation analysis in chondrosarcoma clinical samples block of cell growth suggests that other parallel pathways are also likely to be important. Consistent with our data showing RTK activation, strong and common phosphorylation of the downstream signaling proteins AKT, MEK, and S6 kinase was previously shown using kinase substrate peptide arrays and extracts from chondrosarcoma cell lines and primary cultures (35). Here, we have linked RTK activation in chondrosarcoma cells to PI3K/AKT/mTOR signaling by showing that RTK inhibitors suppress AKT and S6 phosphorylation.…”
Section: Discussionsupporting
confidence: 92%
“…NRAS mutation analysis in chondrosarcoma clinical samples block of cell growth suggests that other parallel pathways are also likely to be important. Consistent with our data showing RTK activation, strong and common phosphorylation of the downstream signaling proteins AKT, MEK, and S6 kinase was previously shown using kinase substrate peptide arrays and extracts from chondrosarcoma cell lines and primary cultures (35). Here, we have linked RTK activation in chondrosarcoma cells to PI3K/AKT/mTOR signaling by showing that RTK inhibitors suppress AKT and S6 phosphorylation.…”
Section: Discussionsupporting
confidence: 92%
“…Effectivity of dasatinib has previously been shown for cells derived from solid tumors as well, including mesenchymal neoplasias, such as GIST and chondrosarcoma (34,35). In chondrosarcoma, growth effects observed upon treatment with dasatinib were not consistently associated with diminished p-(Tyr416)-SRC levels, which makes SRC-independent modes of action probable (35). In contrast, in synovial sarcomas, dephosphorylation of SRC and its targets was a consistent feature detectable upon treatment with dasatinib.…”
Section: Discussionmentioning
confidence: 82%
“…A role for dasatinib is clinically wellestablished in the treatment of chronic myelogenous leukemia and Philadelphia chromosome-positive acute lymphoblastic leukemia (ALL), in which the substance inhibits Abl kinases (32,33). Effectivity of dasatinib has previously been shown for cells derived from solid tumors as well, including mesenchymal neoplasias, such as GIST and chondrosarcoma (34,35). In chondrosarcoma, growth effects observed upon treatment with dasatinib were not consistently associated with diminished p-(Tyr416)-SRC levels, which makes SRC-independent modes of action probable (35).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the therapeutic benefit of dasatinib in preventing the growth and metastasis of sarcomas. In osteosarcoma cell lines, wound-healing, cell migration and TUNEL assays indicated that dasatinib may block cell motility and invasion, and induce apoptosis (45,73). In chondrosarcoma, dasatinib was also capable of decreasing tumor growth, however, it was unable to reduce invasion (73).…”
Section: Clinical Development Of Src Inhibitorsmentioning
confidence: 99%